High plasma dopamine level as a risk factor for atopic dermatitis - Made Swastika Adiguna; Made Wardhana; Ermon Naftali Limbara (Explorer Front, 2019)
Background: Dopamine is responsible for inflammatory response and plays a role in the skin immune system by modulating T-cells, dendritic cells, and keratinocytes which increases skin inflammatory response in atopic dermatitis (AD). Elevation of dopamine level will affect IL-6, IL-8, IL-23, Th-17, and TNF-α, which promotes keratinocyte proliferation and differentiation, infiltration of inflammatory cells, angiogenesis, vasodilation, and skin barrier disruption on AD. Objective: This study aimed to establish whether the increase of plasma dopamine level contributes to a risk factor for AD occurrence. Methods: This is a matched-pair case-control observational analytical study which involves patients with AD and without AD as control. Samples were taken using a consecutive sampling method which fulfilled inclusion and exclusion criteria, matched for gender and age. Plasma dopamine level was measured from venous blood and processed using enzyme-linked immunosorbent assay (ELISA) method. The collected data were then analysed using SPSS version 20.0 with Pearson chi-square test for the odds ratio. Results: A total of 30 samples with AD (case group) and 30 samples without AD (control group) involved in this study. This study proves that plasma dopamine levels in the case group were significantly higher than the control group (p<0.05). Odds ratio for plasma dopamine was 42.2 (95%CI: 9.5-187.2, p < 0.001). Conclusion: This study concludes that high plasma dopamine level is a risk factor for AD.